On-demand Software Management in Sensor Networks using Profiling Techniques - Fuchs, Gerhard; et al. (Proc. of Second ACM International Workshop on Multi-hop Ad Hoc Networks: from theory to reality 2006, 2006)
The heterogeneity and dynamics in terms of hardware and software configurations is steadily increasing in sensor networks. Therefore, software management is becoming one of the most prominent challenges in this domain. We developed a profile-based software management scheme that consists of a dynamic profile-matching algorithm to identify current SW/HW configurations, an on-demand code generation module, and mechanisms for dynamic network-centric reprogramming of sensor nodes. In this demo, we will dynamic node reprogramming based on given objectives (global goals), available sensor nodes, and RPC-style profile matching algorithms. A mobile robot system is employed for decision processes and to store the source code repository. Additionally, techniques for dynamic addressing are included to prevent global pre-configuration of all network nodes.
UnivIS-Import:2015-04-16:Pub.2006.tech.IMMD.IMMD7.ondema
Keywords: Network management; Profiling; Re-configuration; Re-programming; Software management; Wireless sensor network